Diet, exposure to polycyclic aromatic hydrocarbons during pregnancy, and fetal growth: A comparative study of mothers and their fetuses in industrial and urban areas in Southwest Iran. (1st May 2021) - Khalili Doroodzani, Atefeh; Dobaradaran, Sina; Akhbarizadeh, Razegheh; Raeisi, Alireza; Rahmani, Elham; Mahmoodi, Marzieh; Nabipour, Iraj; Keshmiri, Saeed; Darabi, Amir Hossein; Khamisipour, Gholamreza; Mahmudpour, Mehdi; Keshtkar, Mozhgan
Abstract: The presence of polycyclic aromatic hydrocarbons (PAHs) in the fetal environment is a high-priority concern due to the fetus being more sensitive than adults to these ubiquitous xenobiotics. The aim of the present study was to compare the maternal and fetal serum levels of ΣPAHs and their effects on fetal growth in an industrial and an urban area in Southwest Iran. The industrial area was the petrochemical and gas area (PGA) of the Central District of Asaluyeh County and the urban area (UA) was the Central District of Bushehr County, Ninety-nine maternal serum (MS) and 99 cord serum (CS) samples from the PGA and 100 MS and 100 CS samples from the UA were collected during May 2018 to February 2019. The mean concentrations of ΣPAHs were significantly ( p  < 0.05) higher in the PGA than the UA in both MS (157.71 vs. 93.56 μg/L) and CS (155.28 vs. 93.19 μg/L) samples. Naphthalene (NAP) was the predominant PAH detected in all the studied samples. Significant negative associations were found between birth weight and anthracene (ANT) level in MS ( β  = −22.917, p  = 0.032; weight decrement = 22.917 g for a 1 μg/L increase in ANT); head circumference and chrysene (CHR) level in MS ( β  = −0.206, p  = 0.023; head circumference decrement = 0.206 cm for a 1 μg/L increase in CHR); and birth height and NAP level in CS ( β  = −0.20, p  = 0.005; height decrement = 0.20 cm for a 1 μg/L increase in NAP). Maternal diet had a significant effect on the serum levels of PAHs. The results of this study showed that transmission of PAHs from mother to fetus through the cord blood is an important issue and mothers who live in industrial areas and consume PAH-containing foodstuffs, and their fetuses, are more at risk than those living in a non-industrial urban area. Graphical abstract: Image 1 Abstract : Capsule: Comparison of polycyclic aromatic hydrocarbons levels of maternal and cord serum samples.